Comparing CxBladder to Urine Cytology as Adjunct to Cystoscopy in Surveillance of Non-muscle Invasive Bladder Cancer—A Pilot Study - Chai, C. A.; Yeoh, W. S.; Rajandram, R.; Aung, K. P.; Ong, T. A.; Kuppusamy, S.; Nazran, A.; Kumaran, K.; Razack, A. H. A.; Teoh, J. Y. (Frontiers in Surgery, 2021)
Purpose: Guidelines advocate cystoscopy surveillance(CS) for non-muscle invasive bladder cancer(NMIBC) post-resection. However, cystoscopy is operator dependent and may miss upper tract lesions or carcinoma in-situ(CIS). Urine cytology is a common adjunct but lacks sensitivity and specificity in detecting recurrence. A new mRNA biomarker (CxBladder) was compared with urine cytology as an adjunct to cystoscopy in detecting a positive cystoscopy findings during surveillance cystoscopy in our center. Materials and methods: Consented patients older than 18, undergoing CS for NMIBC, provide paired urine samples for cytology and CxBladder test. Patients with positive cystoscopy findings would undergo re-TURBT. Results: Thirty-five patients were enrolled from April to June 2019. Seven contaminated urine samples were excluded. The remaining cohort of 23(82%) males and 5(18%) females had a mean age of 66.69(36-89). Eight(29%) patients with positive cystoscopy finding underwent TURBT. All 8 patients also had positive CxBladder result. This shows that CxBladder has a sensitivity and negative predictive value (NPV) of 100%, specificity of 75% and positive predictive value (PPV) of 62% in predicting a positive cystoscopy finding. TURBT Histo-pathological findings showed 1(4%) low-grade Ta NMIBC, and 7(25%) inflammatory changes. Urine cytology was only positive in 1 patient with a positive cystoscopy finding. This led to a sensitivity of merely 13% and NPV of 74%, while specificity and PPV was 100% in predicting a positive cystoscopy finding. Conclusion: CxBladder had high NPV and sensitivity which accurately predicted suspicious cystoscopy findings leading to further investigation. It has great potential to become a good adjunct to cystoscopy for surveillance of NMIBC.